Water metaphors and polyvalence in the Book of Proverbs - Loader, James Alfred (HTS teologiese studies, 2023)
This article argues that Proverbs 18:4 contains an exceptionally rich use of water as metaphors in sapiential literature. At the same time, the verse illustrates the multivalent applicability of a single proverb. Israel’s natural environment is shortly described as pictured in the biblical texts, suggesting the interplay of water and dry land in the ancient Near East. Water and dryness have ambivalent functions, as both are necessary and both can be dangerous. In order to understand Proverbs 18:4, a short overview of water in ancient Near Eastern texts is generally given and the significance of the multivalent application of representative proverbs is illustrated. Coming to Proverbs 18:4, an interpretation is offered showing a potential of various differing understandings of the water metaphor concentrated in a single proverb. Although such a proverb now exists in a written literary context, it can be used in various contexts, and each time be applied differently in its own right, but with equal validity.Contribution: It is argued that the multifarious use of water as a literary motif in Proverbs entails that both its explicit and its implied use can function literally, metaphorically and even as metaphtonemy, with variegated valid meanings whether in individual proverbs by themselves or as part of larger literary contexts.